Karakteristik Fisik dan Mekanik Kemiri (Aleurites moluccana Wild.) - Robert Sinaga; Desrial -; Dyah Wulandani (PERTETA, 2016)
AbstractIt is very important to know the characteristics of candle nut before designing nut-deshelling machine. This study was conducted to investigate physical and mechanical characteristics of candle nut before analyzing the impact force on the de-shelling process. The result showed that average diameter of candle nut at intercept A (length), B (width) and C (thickness) were 32.55 mm, 29.05 mm and 23.23 mm respectively. The average value of sphericity and roundness of candle nut were 0.86 and 0.65 respectively. At high moisturecontent candle nut had a greater value of compressive strength and resulted a sticky kernel in the shell. Candle nut had 4.96% db moisture content after dried at sun drying for 20 hours. The value of compressive strength from the maximum load during a compression test (rupture force) of candle nut at this moisture content were 1,208 N, 1,198 N and 1,950 N for intercept A, B and C respectively.AbstrakSangat penting untuk mengetahui karakteristik kemiri sebelum mendesain mesin pemecah biji kemiri. Penelitian ini dilakukan untuk mengetahui karakteristik fisik dan mekanik biji sebelum menganalisis gaya tumbukan pada proses pemecahan biji kemiri. Hasil penelitian ini menunjukkan bahwa rata-rata diameter biji kemiri pada intersep A (panjang), B (lebar) dan C (tebal) adalah 32.55 mm, 29.05 mm dan 23.23 mm. Nilai rata-rata kebulatan dan kebundaran biji kemiri adalah 0.86 dan 0.65. Pada tingkat kadar air yang tinggi, kemiri memiliki nilai kekuatan tekan yang lebih besar dan akan menghasilkan inti lengket pada tempurung bagian dalam. Kadar air kemiri mencapai 4.96% bk setelah dijemur di bawah sinar matahariselama 20 jam. Nilai kekuatan maksimum pada saat pemberian uji tekan (rupture force) pada tingkat kadar air tersebut pada intersep A adalah adalah 1,208 N, intersep B 1,198 N dan intersep C 1,950 N.